2016
DOI: 10.1097/md.0000000000004519
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric magnetic resonance imaging and frozen-section analysis efficiently predict upgrading, upstaging, and extraprostatic extension in patients undergoing nerve-sparing robotic-assisted radical prostatectomy

Abstract: To evaluate the role of multiparametric magnetic resonance imaging (mpMRI) in predicting upgrading, upstaging, and extraprostatic extension in patients with low-risk prostate cancer (PCa). MpMRI may reduce positive surgical margins (PSM) and improve nerve-sparing during robotic-assisted radical prostatectomy (RARP) for localized prostate cancer PCa.This was a retrospective, monocentric, observational study. We retrieved the records of patients undergoing RARP from January 2012 to December 2013 at our Instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
2
23
0
1
Order By: Relevance
“…More recently, Lim et al showed that PI‐RADS v2 category 5 lesions were associated with higher Gleason scores and the presence of EPE compared to category 4 lesions. These studies support our observation that higher PI‐RADS v2 scores are associated with EPE . Interobserver agreement for PI‐RADS v2 scoring between radiologists in our study was moderate, which compares favorably with what has been published previously …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More recently, Lim et al showed that PI‐RADS v2 category 5 lesions were associated with higher Gleason scores and the presence of EPE compared to category 4 lesions. These studies support our observation that higher PI‐RADS v2 scores are associated with EPE . Interobserver agreement for PI‐RADS v2 scoring between radiologists in our study was moderate, which compares favorably with what has been published previously …”
Section: Discussionsupporting
confidence: 92%
“…These studies support our observation that higher PI-RADS v2 scores are associated with EPE. 40 Interobserver agreement for PI-RADS v2 scoring between radiologists in our study was moderate, which compares favorably with what has been published previously. 41,42 Tumor size and length of capsular contact were both larger in tumors with EPE in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The established preoperative clinical variables, for example, digital rectal examination, serum prostatic‐specific antigen, and the Gleason score obtained from biopsy, are used to plan the surgical technique . Recently, several reports have demonstrated that preoperative multiparametric magnetic resonance imaging (MRI) significantly improved decision‐making regarding whether to preserve or resect the neurovascular bundle at radical prostatectomy . In addition, Kitajima et al demonstrated that, after NS radical prostatectomy, the diffusion tensor imaging technique of MRI could visualize changes in the numbers of periprostatic nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies were retrospective (74%) and only five studies (26%) were prospective in nature. Furthermore, the studies were performed mainly in Germany (seven studies) , the UK (four studies) , USA (three studies) , Turkey (two studies) , Italy , Romania , and Norway (one study each). The sample size (considering only the patients undergoing intraoperative FS) in the included studies ranged from 40 to 5392 patients.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…A total of 19 articles reporting on NS‐zone sampling techniques and NVB secondary resection were published between 2010 and 2019 . Table summarises all the studies reporting FS sampling and secondary resection of a PSM at the NVB.…”
Section: Evidence Synthesismentioning
confidence: 99%